The earliest stimulation program applied for mothes - Risco Aguilar, Marissa (2004)
A program for early aproachment of 6th to 2 months aged children was performed with 50 mothers who lived in urban-marginal communities from Piura and Lima. They had children aged 6 to 24 months, low income, and poor instruction. They were enabled and trained in use with handbook “Stimulating your child means aiding him to learn with love”. Children´s development was assessed before training their mothers and two months later. At former 26.9% children were at Risk level and further in lowed at 7.7%. Meaning improvement was found in some areas, i.e., success in expressive language increased to 76.9% from 53.9%.